Renal K+ retention in physiological circumstances: focus on adaptation of the distal nephron and cross-talk with Na+ transport systems - Lasaad, Samia; Crambert, Gilles (Frontiers in Physiology, 2023)
Consumption of salt (NaCl) and potassium (K + ) have been completely modified, switching from a rich-K + /low NaCl diet in the hunter-gatherer population to the opposite in the modern, westernized population. The ability to conserve K + is crucial to maintain plasma K + concentration into a physiological range when dietary K + intake is decreased. Moreover, a chronic reduction of the K + intake is correlated with an increased blood pressure, an effect worsened by high Na + diet. The renal adaptation to low K + diet in order to maintain the plasma K + level in the normal range is complex and interconnected with the mechanisms of the Na + balance. In this short review, we will recapitulate the general mechanisms allowing to maintain the plasma K + value in the normal range, when there is a necessity to retain K + (response to low-K + diet and adaptation to gestation), by focusing on the processes occurring in the most distal part of the nephron. We will particularly outline the mechanisms of K + reabsorption and discuss the consequences of its absence on the Na + transport systems and the regulation of the extracellular compartment volume and blood pressure.